2016
DOI: 10.1080/15384047.2016.1250988
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-activated cytotoxicity of benznidazole against clonogenic tumor cells

Abstract: Solid tumors contain numerous regions with insufficient oxygen concentrations, a condition termed hypoxia. Tumor hypoxia is significantly associated with metastasis, refractory to conventional cancer therapies, and poor patient survival. Therefore, eradication of hypoxic tumor cells will likely have significant impact on the overall progression-free patient survival. This article reports a new discovery that Benznidazole, a bioreductive drug currently used to treat Chagas disease caused by the parasitic protoz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The clonogenic assay is based on our previously published protocols [ 22 , 28 ]. Briefly, tumor cells were plated at 600 cells/well for MDA-MB-231 cells and at 1000 cells/well for MCF7 cells in 6-well plates and incubated for 10 to 14 days.…”
Section: Methodsmentioning
confidence: 99%
“…The clonogenic assay is based on our previously published protocols [ 22 , 28 ]. Briefly, tumor cells were plated at 600 cells/well for MDA-MB-231 cells and at 1000 cells/well for MCF7 cells in 6-well plates and incubated for 10 to 14 days.…”
Section: Methodsmentioning
confidence: 99%
“…The clonogenic assay is based on our previously published protocols 52,54 . Briefly, tumor cells were plated at 600 cells/well for MDA-MB-231 cells and at 1000 cells/well for SK-N-BE(2)C cells in 6-well plates and incubated for 10 to 14 days.…”
Section: Methodsmentioning
confidence: 99%
“…While benznidazole has been found to be mutagenic and associated with lymphomas in animal studies (Teixeira et al, 1990), others have observed that the compound caused a reduction in nitric oxide synthesis in treated infected mice; consequently, this contributed to protect against T. cruzi-induced oxidative DNA damage, minimizing parasite-induced genotoxicity (Ribeiro et al, 2007). Li et al (2016a) have found that benznidazole is a hypoxiaactivated cytotoxin that can specifically kill clonogenic tumor cells that are under severe hypoxic conditions or tumor-initiating cancer cells It probably acts by inducing double-strand breaks, just as on T. cruzi DNA; the same has also been reported for nifurtimox (Li et al, 2017). In addition, some clinical observations do not indicate modifications in the incidence of neoplasms in CD patients treated with benznidazole (Andrade et al, 2003).…”
Section: Pharmacological Intervention For Chagas Disease and Cancermentioning
confidence: 99%